Fitness Level Influences White Matter Microstructure in Postmenopausal Women - Harasym, Diana; Turco, Claudia V.; Nicolini, Chiara; Toepp, Stephen L.; Jenkins, E. Madison; Gibala, Martin J.; Noseworthy, Michael D.; Nelson, Aimee J. (Frontiers in Aging Neuroscience, 2020)
Aerobic exercise has both neuroprotective and neurorehabilitative benefits. However, the underlying mechanisms are not fully understood, including in postmenopausal women, who are at increased risk of age-related disorders such as Alzheimer’s disease and stroke. To advance our understanding of the potential neurological benefits of aerobic exercise in aging women, we examined anatomical and functional responses that may differentiate women of varying cardiorespiratory fitness using neuroimaging and neurophysiology. A total of 35 healthy postmenopausal women were recruited (59±3 years) and cardiorespiratory fitness estimated (22-70 mL/kg/min). Transcranial magnetic stimulation was used to assess gamma-aminobutyric acid (GABA) and glutamate (Glu) receptor function in the primary motor cortex (M1), and magnetic resonance spectroscopy (MRS) was used to quantify GABA and Glu concentrations in M1. Magnetic resonance imaging was used to assess mean cortical thickness (MCT) of sensorimotor and frontal regions, while the microstructure of sensorimotor and other white matter tracts were evaluated through diffusion tensor imaging. Regression analysis revealed that higher fitness levels were associated with improved microstructure in pre-motor and sensory tracts, and the hippocampal cingulum. Fitness level was not associated with MCT, MRS or neurophysiology measures. These data indicate that, in postmenopausal women, higher cardiorespiratory fitness is linked with preserved selective white matter microstructure and include areas that influence sensorimotor control and memory.